2017
DOI: 10.1111/mec.14069
|View full text |Cite
|
Sign up to set email alerts
|

Extreme genetic structure in a social bird species despite high dispersal capacity

Abstract: Social barriers have been shown to reduce gene flow and contribute to genetic structure among populations in species with high cognitive capacity and complex societies, such as cetaceans, apes and humans. In birds, high dispersal capacity is thought to prevent population divergence unless major geographical or habitat barriers induce isolation patterns by dispersal, colonization or adaptation limitation. We report that Iberian populations of the red-billed chough, a social, gregarious corvid with high dispersa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 97 publications
1
26
0
Order By: Relevance
“…Our results reveal that current chough populations in Iberia, the in- ranges, also consistent with geography, which confirms that effective dispersal in this species is low despite its high dispersal capacity, as previously documented from an extensive study across Iberia (Morinha, Dávila, et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
“…Our results reveal that current chough populations in Iberia, the in- ranges, also consistent with geography, which confirms that effective dispersal in this species is low despite its high dispersal capacity, as previously documented from an extensive study across Iberia (Morinha, Dávila, et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
“…There is only one documented dispersal between the north and south sides of Rota: a female dispersed 12,687 m while all other dispersals were less than 5000 m [67]. While corvids are generally thought to be capable of long-distance movements, in a number of species a surprising degree of small-scale population structure has been detected [68,69,70,71]. One species that has a high dispersal capacity, yet unusual genetic structure, is the Red-billed Chough ( Pyrrhocorax pyrrhocorax ) in the Iberian Peninsula.…”
Section: Discussionmentioning
confidence: 99%
“…The high levels of spatial interaction suggest flocking behavior; Kittlitz’s plovers exhibit complex gregarious social behavior where individual plovers join to flock for feeding and resting; even members of breeding pairs join flocks ( Urban et al 1986 ; Hockey et al 2005 ), but the relative numbers of paired and unpaired individuals within these flocks is not currently known. This greater degree of sociality increases the potential for high levels of gene flow across a population; however, a recent study of genetic structure in the social, but monogamous, red-billed chough Pyrrhocorax pyrrhocorax found strongly segregated populations ( Morinha et al 2017 ), suggesting both mating opportunities and social interaction are needed to facilitate high levels of gene flow. Flocking behavior may facilitate gene flow through lower energy costs associated with mate searching due to high densities, and reduced risk of predation while searching ( DeRivera et al 2003 ; Kasumovic et al 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many species of birds and mammals disperse to enhance mating opportunities and reproductive success; and access to mates, resources, and the avoidance of inbreeding are important in promoting sex-specific dispersal ( Greenwood 1980 ; Lenormand 2002 ; Trochet et al 2016 ). However, fine-scale continuous events, such as the social environment, spatial distribution, and mate search behavior, are often overlooked ( Skrade and Dinsmore 2010 ; Wey et al 2015 ) in favor of rarer, large-scale dispersal events which cannot explain observed levels of gene flow alone ( D’Urban-Jackson et al 2017 , Morinha et al 2017 ). Individual movement patterns and space use strategies can influence social interaction as well as mating success, and hence gene flow ( Duvall 1997 ; Sih et al 2009 ; McGuire 2013 ).…”
Section: Introductionmentioning
confidence: 99%